Pathogenicity of fungal and bacterial bioinsecticides against adult peach fruit fly, Bactrocera zonata (Saunders) (Diptera: Tephritidae) admixed with adult diet under controlled conditions - Muhammad Junaid Nisar (SpringerOpen, 2021)
Abstract Background The peach fruit fly, Bactrocera zonata (Saunders) (Diptera: Tephritidae), is a serious polyphagous pest of fruits and vegetables. Chemical management of B. zonata in fruits results in toxic residues that have adverse health effects on consumers resulting in increased demand for eco-friendly approaches. Laboratory bioassay was conducted to determine the pathogenicity of fungal and bacterial biopesticides against B. zonata. Results The pathogenicity of all tested bioinsecticides revealed that the maximum concentration (1 × 108 CFU ml−1) of Metarhizium anisopliae, Beauveria bassiana, Lecanicillium lecanii and Bacillus thuringiensis caused 95.8–100%, 95.9–97.9%, 32.7–39.6%, and 20.0–22.4% mortality in B. zonata, respectively at 7 d post-application interval (PAI) as compared to mortality demonstrated by the same concentration at 5 d PAI. All tested microbial insecticides induced statistically similar mortality in both male and female B. zonata at each concentration for the same PAI. Correlation coefficient (r) values reveal that concentrations of each microbial insecticide had a high positive correlation with mortalities of male and female B. zonata. Regression parameters reveal that concentrations of tested microbial insecticides had significant linear relationship with and explained significant variability in B. zonata mortality (P < 0.05). Results also revealed that M. anisopliae was proved more pathogenic to males and females of B. zonata demonstrating the least LC50 values (5.48 × 103, and 6.17 × 103 CFU ml−1, respectively) 7 d post-application intervals, followed by B. bassiana which explained LC50 value of 1.14 × 104 CFU and 1.15 × 105 CFU ml−1 for B. zonata males and females, respectively, at the same period of application, but less than that of L. lecanii (2.77 × 109 and 1.43 × 109 CFU ml−1) and then B. thuringiensis (3.40 × 1010 and 1.39 × 1010 CFU ml−1) for the males and females, respectively, at 7 d PAIs. Conclusion Metarhizium anisopliae incorporated adult diet was proved more effective against B. zonata, followed by B. bassiana, L. lecanii, and B. thuringiensis. Hence, M. anisopliae can be recommended for incorporating in bait-traps to develop attract-and-kill technology for B. zonata.